Integrasi Pembelajaran Praktis melalui Kegiatan Relawan Pajak dalam Kolaborasi Mahasiswa dan KPP Pratama Jember pada Asistensi Pelaporan SPT Tahunan - Anni Mustawanda Puri Rasendriya; Fitria Nur Layla; Lailatul Munawaroh (MASALIQ, 2025)
This study is driven by the growing demand from the labor market for universities to produce graduates who are not only theoretically proficient but also practically competent. The research aims to analyze the collaboration between student volunteers and the Jember Primary Tax Office (KPP Pratama Jember) through the Tax Volunteer Program as a practical learning model in assisting individual taxpayers with the submission of their Annual Tax Returns (SPT). A case study approach was employed, with data collected through observation, interviews, and documentation. Participants included student volunteers from local universities and tax officers at KPP Pratama Jember involved in the 2024 tax season. The findings indicate that student involvement significantly contributed to increased taxpayer compliance and enhanced students' professional skills, particularly in communication, service, and tax-related problem-solving. Institutionally, the program helped expand the service reach of the tax office and improved the efficiency of annual tax return reporting. This collaboration illustrates a strategic synergy between higher education institutions and tax authorities in promoting tax literacy and developing competent, ethical human resources. The study concludes that sustainable development of the program requires structured training and policy support. Its practical implications include strengthening partnerships and expanding cross-disciplinary participation in tax assistance activities as a strategy for advancing vocational learning in higher education.